2006
DOI: 10.2223/jped.1462
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function assessment in children and teenagers before and after surgical treatment for rheumatic valve disease

Abstract: Objective: To assess pulmonary function in children and adolescents subjected to correction of rheumatic valve disease in order to quantify changes caused by factors inherent to surgery and rheumatic heart disease.Methods: This was a longitudinal and quantitative intervention study, undertaken at a childrens hospital that is a center of excellence for the state of Pernambuco (Instituto Materno Infantil de Pernambuco), between December 2004 and May 2005. Eighteen children suffering from rheumatic fever and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The comparison of respiratory function variables intragroup over time in this study confirms the findings of the study by Caséca et al 13 , a prospective study that evaluated children who underwent mitral valve replacement or reconstruction. The authors demonstrated that PEF and lung volume and capacity values evaluated in the post-operative period, except MV, remained significantly deteriorated from the 1 st to the 5 th POD compared to pre-operative values.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The comparison of respiratory function variables intragroup over time in this study confirms the findings of the study by Caséca et al 13 , a prospective study that evaluated children who underwent mitral valve replacement or reconstruction. The authors demonstrated that PEF and lung volume and capacity values evaluated in the post-operative period, except MV, remained significantly deteriorated from the 1 st to the 5 th POD compared to pre-operative values.…”
Section: Discussionsupporting
confidence: 91%
“…The authors demonstrated that PEF and lung volume and capacity values evaluated in the post-operative period, except MV, remained significantly deteriorated from the 1 st to the 5 th POD compared to pre-operative values. In the present study, only MIP returned to pre-operative values on the 5 th POD, a variable that was not analyzed in the study by Caséca et al 13 cited above.…”
Section: Discussionmentioning
confidence: 62%
“…The spirometric parameters were interpreted on the basis of the equations devised by Pereira et al (11) A Wright spirometer (British Oxygen Company, London, UK) was attached to the incentive spirometer and to the BS mask, allowing the inspiratory volume to be measured during the procedures. (12) Postoperative risk Figure 2 shows the mean inspiratory volumes for the two groups at the various time points evaluated. In the IS and BS groups, inspiratory volume was significantly lower on postoperative day 1 than in the preoperative evaluation (0.82 L vs. 2.29 L and 1.34 L vs. 2.56 L, respectively; p < 0.001 for both).…”
Section: Resultsmentioning
confidence: 99%
“…The only study in the literature addressing lung function of children and adolescents with rheumatic heart disease reported spirometry values below expectations, but subjects had been evaluated in pre- and postoperative periods of heart surgery, which may have affected the results negatively. 27 …”
Section: Discussionmentioning
confidence: 99%